Biomaterial 3D collagen I gel culture model: A novel approach to investigate tumorigenesis and dormancy of bladder cancer cells induced by tumor microenvironment. (October 2020) - Qiu, Yaqi; Qiu, Shi; Deng, Linghui; Nie, Ling; Gong, Lina; Liao, Xinyang; Zheng, Xiaonan; Jin, Kun; Li, Jiakun; Tu, Xiang; Liu, Liangren; Liu, Zhenhua; et al.
Abstract: The high potential for cancer relapse has emerged as a crucial challenge of human bladder cancer treatment. To date, those stem-like bladder cancer cells (BCSCs) have been considered as seeds that induce frequent tumor recurrence. However, the cell origin of cancer stem cells (CSCs) is still a controversial issue, due in part to the findings that CSCs not only origin from normal stem cells but also converted from differentiated tumor cells. Here, we describe a biomaterial 3D collagen I gel culture system, where non-tumorigenic cells can obtain tumorigenic potential and revert back into CSCs through the integrin α2β1/PI3K/AKT/NF-κB cascade, resulting in the tumorigenesis in bladder tissues. Furthermore, inhibiting this integrin α2β1/PI3K/AKT/NF-κB signal pathways can significantly impair the tumorigenic capacity of CSCs. Simultaneously, in vivo studies demonstrate that IFN-γ secreted by T cells can trigger those CSCs into dormancy through the IDO/Kyn/AHR/P27 cascade, which elicit chemotherapy resistance and cancer relapse. To address the challenges of suppressing bladder tumor growth and preventing tumor reoccurrence, we use IDO and integrin α2β1 signal pathway inhibitors combine with chemotherapeutic agents to awaken dormant bladder CSCs and inhibit their tumorigenic ability as well as effectively eliminate CSCs. The therapeutic approaches we propose provide new insights for eradicating tumors and reducing bladder cancer relapse after therapy.